Predicting Professional Entrepreneurial Intention Through Core Determinants of Entrepreneurial Attitude - Sunanto Sunanto; Kasmad Kasmad; Jeni Andriani (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2026)
The level of entrepreneurship among professional pharmacists is comparable to Indonesia's overall level of entrepreneurship, which is relatively low. This phenomenon is associated with entrepreneurial marketing behavior focused on Entrepreneurial Intention. For the first time in the context of professional pharmacists in Greater Jakarta, the influence of Entrepreneurial Education (EE) and Entrepreneurial Self-efficacy (ESE) on Entrepreneurial Attitude (EA) and its implications for Entrepreneurial Intention (EI) was observed using the Theory of Planned Behavior (TPB). Through proportional random sampling, 391 pharmacists were selected using the Slovin formula (5% margin of error). Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) were used for quantitative analysis. The findings showed that ESE was the most powerful factor, with EE, ESE and EA all having positive and substantial direct effects on EI. The mediating effect of EA was evident in the influence of ESE on EI, but not EE. This study's novel approach lies in its consideration of the unique characteristics of healthcare entrepreneurship, which differ from general entrepreneurship due to constraints such as the complexity of the dual role. This research provides business insights to promote EI as necessity among professional pharmacists.